2019
DOI: 10.3390/jcm8122122
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Rich Plasma as Adjuvant Therapy for Recurrent Vesicovaginal Fistula: A Prospective Case Series

Abstract: Vesicovaginal fistula (VVF) is the nonphysiological communication between the bladder and vagina, and surgical closure is the gold treatment standard. Despite that successful closure occurs in around 85% of patients after the first repair, recurrence remains a highly distressing complication for patients and surgeons. The aim of our study was to evaluate the efficacy of a platelet-rich plasma (PRP) injection as a supportive treatment in the surgical repair of recurrent VVF. Between January 2018 and July 2019, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…The preliminary results of the research of Streit-Ciećkiewicz et al on patients with recurrent vesicovaginal fistulas showed the successful surgical closure of a fistula 4–6 weeks after PRP injection with no complications or adverse reactions [ 7 ]. In this research, an attempt was made to find factors that might have had predictive value when assigning the patient surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The preliminary results of the research of Streit-Ciećkiewicz et al on patients with recurrent vesicovaginal fistulas showed the successful surgical closure of a fistula 4–6 weeks after PRP injection with no complications or adverse reactions [ 7 ]. In this research, an attempt was made to find factors that might have had predictive value when assigning the patient surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In December 2019, the patent qualified for a platelet-rich plasma (PRP) injection procedure of the fistula edges. This operation is described elsewhere [ 7 ]. In February 2020 (7 weeks after the injection), a 2nd Latzko reconstructive procedure was performed.…”
Section: Case Reportmentioning
confidence: 99%
“…In cases with increase residual rate, or decreased surgical rate, a few new therapeutic techniques are very helpful and promising. Many conducted studies arising from the current bibliography, such as blood-based products (autologous platelet-rich plasma and fibrin glue) managed to establish new standards and accomplish their scope [18]. Sharma et al first described the use of endoscopic injection of fibrin concerning the therapeutic strategy of VVF, not depicting any potential postoperative complications [19].…”
Section: Discussionmentioning
confidence: 99%
“…Data about PRP application in the treatment of recurrent VVF was published elsewhere. 12 Each patient was classified according to Sims, Mahfouz, Chassar Moir, McConnachie, Bird, Gray, Lawson, Hamlin and Nicholson, Waaldijk, Goh, Arrowsmith, Tafesse, and WHO systems. [4][5][6][7][8][9][10][11]13 Patients were dichotomized into two groups: women with primary and with secondary VVF.…”
Section: Methodsmentioning
confidence: 99%
“…The tubes were centrifuged with the Arthrex Angel System® kit (Arthrex Inc.), resulting in 4–6 ml PRP volumes. Data about PRP application in the treatment of recurrent VVF was published elsewhere 12 …”
Section: Methodsmentioning
confidence: 99%